2012
DOI: 10.4103/0019-509x.104489
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth in Iranian cancer patients

Abstract: The findings of this study suggest that Iranian cancer patients experience a moderate to high level of posttraumatic growth and confirm the hypothesis that the level of posttraumatic growth in non-Western cancer patients is more than that of Western cancer patients. Although, assessing the reasons for this difference needs more investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…The remaining ones found a direct relationship between undergoing chemotherapy and PTG compared to no chemotherapy, radiotherapy, or their combination, respectfully . Regarding radiotherapy, one study (which used the Persian version of PTGI) found a direct relationship between PTG and this treatment versus chemotherapy or surgery; while another one found an inverse relationship as compared to surgery …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining ones found a direct relationship between undergoing chemotherapy and PTG compared to no chemotherapy, radiotherapy, or their combination, respectfully . Regarding radiotherapy, one study (which used the Persian version of PTGI) found a direct relationship between PTG and this treatment versus chemotherapy or surgery; while another one found an inverse relationship as compared to surgery …”
Section: Resultsmentioning
confidence: 99%
“…Specifically, while most articles distinguished PTG from other constructs, some others did not. For example, some authors considered PTG and BF as synonyms (eg, Rahmani et al; Labelle et al), and they used the PTGI, the BFS, or the Stress‐Related Growth Scale. In other articles, authors did not distinguish among PTG, BF, and meaning (eg, Bower et al; Heinrichs et al) and used the PTGI to assess all of them.…”
Section: Discussionmentioning
confidence: 99%
“…PTG has been found to be inversely correlated to quality of life in cancer patients in three studies . In addition, studies have demonstrated that quality of life in head and neck cancer patients significantly deteriorates during radiotherapy, surgery and chemotherapy but is then followed by gradual recovery and improvement up to 12 months after treatment . Improved quality of life following treatment possibly contributed to a decrease in PTG at follow‐up.…”
Section: Discussionmentioning
confidence: 98%
“…It consists of five components, that is, spiritual development, new possibilities in life, better appreciation of life, greater sense of personal strength and improved relationships with others . Several factors associated with increased PTG in cancer patients include younger age, highly educated patients , recurrence, severity of cancer and coping styles such as problem solving, adaptive coping, meaning making and benefit finding . PTG is also reported amongst Malaysian cancer patients .…”
Section: Introductionmentioning
confidence: 99%
“…Triplett et al reported that the internal reliability of the scale was 0.90 and the test-retest consistency with a two-month interval was 0.71 (18,28). The PTGI was translated into Persian by Mahmoudi (2008) and then revised and adapted by Mahmoudi et al According to the results of PTGI construct analysis, three factors were confirmed including changes in the relationship with others (α = 0.86), philosophy of life (α = 0.87) and self-perception (α = 0.88) in an Iranian population (29,30).…”
Section: Posttraumatic Growth Inventory (Ptgi)mentioning
confidence: 99%